Role of Religious Institutions in American to Strengthening Islamic Religion - Fauziyah, Nurul; Ismaita, Annisa Natasya; Ramadhanti, Aulia (Munazzama: Journal of Islamic Management and Pilgrimage, 2025)
The United States possesses a strategically significant geographical location, bordered by the Atlantic Ocean to the east and the Pacific Ocean to the west. This unique positioning has made the country a destination for immigrants from various nations, including Muslim communities. This study aims to explore the historical foundations and development of Islam in the United States, particularly through the contributions of religious institutions and communities that promote and strengthen Islamic teachings. The research utilizes a library-based methodology with a qualitative approach, drawing from books, journals, and official reports relevant to the topic. The findings indicate that, while Islam remains a minority religion in America, its number of adherents continues to grow. This phenomenon is closely tied to the active roles played by religious organizations such as CAIR, ISNA, MSA, and FIMA, which support education, advocacy, and interfaith dialogue. Furthermore, global incidents, such as the attacks on September 11, 2001, have served as significant turning points in increasing public interest in Islam. These institutions are crucial in shaping a positive image of Islam within America's diverse society.